How to do Things with Screens? Anti-Pornography Feminism and Censorship - Denis Ramond (Revue LISA)
Is it possible to condemn certain forms of expression without being seen as a moralist? In order to get around the emphasis that American jurisprudence places on freedom of speech, some antipornography feminists have used the theory of speech acts to demonstrate the wrongs that pornographic representations can inflict on women. If pornography has the power to silence women by its mere existence, then it is possible to fight against it for the sake of freedom of expression. This article aims to show that the application of the theory of speech acts to pornography is based on a strategic confusion between the juridical and linguistic meanings of the term “speech”. However, the feminist argument forcefully emphasizes the ambiguities of the notion of “freedom of speech” when the protection of certain non-discursive forms of expression, such as pornographic representations is at stake.